Pengaruh Kompos Jerami Padi untuk Efisiensi Urea pada Produksi Padi di Kerambitan, Tabanan - Arthagama, I Dewa Made; Narka, I Wayan; Bimantara, Putu Oki (Agrotrop : Journal on Agriculture Science; Vol 15 No 1 (2025), 2025)
The Effect of Rice Straw Compost on Urea Efficiency in Rice Production in Kerambitan, Tabanan.  This research, aims to find the efficiency of Urea fertilization, and also aims to improve several soil chemical properties. This research is a field experiment conducted in Subak Pelem Kerambitan, Tabanan. Using a simple randomized block design (RBD), consisting of rice straw compost and urea fertilizer in different formulation packages in this study. The treatments tried were: KoUo (without fertilizer), KoU1 (300 kg Urea ha -1 ), K1U2 (2.5 tons of rice straw compost+250 kg Urea ha -1 ), K2U3 (5 tons of rice straw compost+200 kg Urea ha -1 ), K3U4 (7.5 tons of rice straw compost+150 kg Urea ha -1 ), K4U5 (10 tons of rice straw compost+100 kg Urea ha -1 ), K5U6 (12.5 tons of rice straw compost+50 kg Urea ha -1 ), K6U7 (15 tons of rice straw compost+0 kg Urea ha -1 ). The results of the study showed that the distribution of straw compost dosage packages and urea have a very significant effect on rice growth and yield. The K2U3 treatment package = (5 tons of rice straw compost + 200 kg Urea ha -1 gives the highest yield of harvested dry grain per ha, namely 7.3 tons ha -1 compared to control, namely 5.6 tons so that the application compost can make it more efficient to apply urea 30.25% ha -1 with an increase in yield of 30.36% ha -1 . Changes in the chemical properties of the soil are getting better due to the influence of compost rice straw and urea, namely the soil pH is somewhat neutral and the CEC of the soil is relatively high.